ANALYSIS OF SOCIODRAMA METHOD ON EMPATHY BEHAVIOR OF 5-6 YEARS OLD CHILDREN IN TK DHARMA WANITA BAKONGAN TIMUR, SOUTH ACEH REGENCY - Ilham Septian; Nur Asiyah; Musdiani; Riza Oktariana (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Empathy is one aspect that must be optimally instilled in children from an early age. Empathy is the ability of an individual or person to understand and feel the feelings of others and react appropriately to other people's feelings. The formulation in this research is how to implement the sociodrama method on the ability to behave empathetically in group B children of the Dharma Wanita TK Bakongan Timur. What are the obstacles to the sociodrama method on the ability to behave empathetically in group B children of Dharma Wanita TK Bakongan Timur. The research method used in this research is descriptive qualitative. The subjects of this research were 2 class teachers. Data collection techniques using interviews. The results of the research explain that in general the children's empathy abilities at the Dharma Wanita Bakotim Kindergarten are going well, so this can be seen in learning using the sociodrama method given by the teacher. Teachers use various media that are appropriate to the child's developmental stages. Children who have difficulty developing empathy will be given special attention by teachers. Special attention to children who experience difficulties in developing their empathy, namely by taking a special approach and providing solutions to the obstacles faced by the child. One of the factors that influence the development of children's empathy is the social interaction factor between one child and another when learning science in class. Apart from that, it is also influenced by the role of parents by providing support in shaping the child's character at home.